Training and Retraining Policies for Civil Servants in Vietnam - Khanh, Tran Thi Bao (Journal of Ecohumanism, 2024)
In practice of civil servant management in countries, training and retraining policies are developed and implemented as a main measure to improve the quality of civil servants, then build up a team of qualified and capable civil servants for serving the people. This study develops a theoretical framework on training and retraining policies and considers the impact of these policies on the quality of Vietnamese civil servants. The research model is developed with independent scales/variables "Training policies", "Retraining policies" and dependent scale/variable "The quality of civil servants". A direct survey was conducted with 350 commune-level civil servants from 5 provinces representing 3 regions of Vietnam, including: Thai Nguyen province, Lang Son province (Northern region), Quang Binh province (Central region), Binh Duong province, Bac Lieu province (Southern). The results show that the implementation of training policies to update and supplement working knowledge and skills for civil servants has not been effective and received little recognition from civil servants in localities; The implementation of training policies to update and supplement working knowledge and skills for civil servants has not been effective. The findings suggest solutions to make the more effective implementation of training and retraining policies for civil servants in Vietnam.